Run Away or Stick Together? The Impact of Organization-Specific Adverse Events on Alliance Partner Defection - Bruyaka, Olga; Philippe, Déborah; Castañer, Xavier (Academy of Management Review, 2018)
Alliances are interorganizational relationships wherein partners agree to engage in joint action and share benefits and burdens. But when might an adverse event that strikes one partner become too burdensome for another partner? Extant theories of alliance instability provide incomplete answers, which is problematic: for stricken organizations, anticipating whether their nonstricken partners will remain in the alliance can be essential for survival. Integrating insights from the alliance dynamics literature and organizational stigma literature, we theorize about how an organization-specific adverse event affects a nonstricken partner’s decision to continue with or defect from an alliance by considering factors that shift the balance between cohesive and disruptive forces. We propose that high stigmatization risk will increase the probability of partner defection through two disruptive mechanisms: relational uncertainty and stigma anxiety. Building on the idea that the same factors contributing to alliance formation may also condition partner defection, we theorize about the roles of partner resource interdependencies, relational embeddedness, and perceived partner similarity in amplifying or attenuating disruptive mechanisms triggered by an adverse event. We extend the research on partner defection and alliance instability by advancing an event-based view of alliance instability and specifying the conditions under which an alliance partner might defect.